2012
DOI: 10.1002/pon.3065
|View full text |Cite
|
Sign up to set email alerts
|

Mental adjustment at different phases in breast cancer trajectory: re‐examination of factor structure of the Mini‐MAC and its correlation with distress

Abstract: The five-factor structure represents a more psychometrically sound measure of psychological adjustment in the current data set. The findings also support the argument that the relationships between coping and distress vary, to some degree, at different phases in the cancer trajectory. FS is only a positive predictor of psychological adjustment among newly diagnosed patients. Because of the exclusion of two items, FA showed a positive correlation with distress, a result that contradicts previous findings. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 31 publications
6
25
0
3
Order By: Relevance
“…Figure 2 illustrates distress levels among patients who received their diagnoses at varying intervals of time. The findings in Figure 2 are consistent with previous research that has demonstrated the fluctuation of distress levels over the course of coping with cancer, which may be due to the uncertainty surrounding cancer treatment (Chambers et al, 2014; Lam, Shing, Bonanno, Mancini, & Fielding, 2012; Nosarti, Roberts, Crayford, McKenzie, & David, 2002; Wang, Tu, Liu, Yeh, & Hsu, 2013; Ziegler et al, 2011). During the first week, patients may be feeling numb or in a state of derealization before they have fully processed the diagnosis (National Cancer Institute, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Figure 2 illustrates distress levels among patients who received their diagnoses at varying intervals of time. The findings in Figure 2 are consistent with previous research that has demonstrated the fluctuation of distress levels over the course of coping with cancer, which may be due to the uncertainty surrounding cancer treatment (Chambers et al, 2014; Lam, Shing, Bonanno, Mancini, & Fielding, 2012; Nosarti, Roberts, Crayford, McKenzie, & David, 2002; Wang, Tu, Liu, Yeh, & Hsu, 2013; Ziegler et al, 2011). During the first week, patients may be feeling numb or in a state of derealization before they have fully processed the diagnosis (National Cancer Institute, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Scores range from 7 to 28. The Chinese version of the HADS has been widely used, and it has demonstrated good internal consistency and validity among cancer patients . The Cronbach's α coefficients in the present sample for the anxiety and depression subscales were .82, .80, .87, and .89, and .65, .77, .72, .77 at T1–T4, respectively.…”
Section: Methodsmentioning
confidence: 60%
“…The short version of the Mental Adjustment to Cancer Scale (Mini-MAC) was administered to measure the following coping strategies: helplessness/hopelessness, anxious preoccupation, fighting spirit, cognitive avoidance, and fatalism (Grassi et al, 2005;Wang, Tu, Liu, Yeh & Hsu, 2013). It is a self-report scale of 29 items, each question rated on a 4-point Likert scale, from 1 ("definitely does not apply to me"), to 4 ("definitely applies to me").…”
Section: Coping Strategiesmentioning
confidence: 99%